Uno strano oggetto per la sociologia: l’attenzione come processo sociale - Campo, Enrico (SocietàMutamentoPolitica, 2023)
Considered a crucial resource, to be exploited for profit or to be protected as a common good, attention has attracted the interest of many disciplines. Despite this, sociology has not yet proposed a systematic analysis of it. The goal of this paper is to show the sociological relevance and heuristic utility of the concept of attention. In the first part, an initial definition of ‘attention’, in relation especially to the concepts of selection and limitation of attentional resources, is provided. Then, the most recent and relevant perspectives that have elected attention as an object of sociological investigation are discussed: the school of cognitive sociology that refers to the figure of Eviatar Zerubavel, the perspectives that look at attention as a resource and Dominique Boullier’s idea of ‘regimes of attention’. Overall, it is shown how adopting a particular metaphor for the study of attention tends to implicitly guide the choice of the elements considered relevant to the observed phenomenon. Therefore, the limitations and potentialities of the different perspectives are analyzed, the points of convergence are explored, and, in conclusion, possible future lines of research are mentioned.